Simple methods of engineering calculation for solving heat transfer problems - Kalis, H.; Kangro, I. (Mathematical Modelling and Analysis, 2003)
There are well‐known numerical methods for solving the initial‐boundary value problems for partial differential equations. We mention only some of them: finite difference method (FDM), finite element method (FEM), boundary element method (BEM), Galerkin type methods and others. In the given work FDM and BEM are considered for determination a distribution of heat in the multilayer media. These methods were used for the reduction of the 1D heat transfer problem described by a partial differential equation to an initial‐value problem for a system of ordinary differential equations (ODEs). Such a procedure allows us to obtain a simple engineering algorithm for solving heat transfer equation in multilayered domain. In a stationary case the exact finite difference scheme is obtained. An inverse problem is also solved. The heat transfer coefficients are found and temperatures in the interior layers depending on the given temperatures inside and outside of a domain are obtained. Paprastieji inžinerinio skaičiaimo metodai šilumos laidumo uždaviniams spręsti Santrauka. Darbe nagrinėjami du ‐ baigtinių skirtumų ir kraštinių elementų ‐ metodai šilumos pasiskirstymo daugiasluoksnėje aplinkoje uždaviniams spręsti. Šiais metodais dviejų kintamųjų uždavinys dalinėmis išvestinėmis pakeičiamas pradiniu ‐ kraštiniu paprastųjų diferencialinių lygčių sistemos uždaviniu. Tokia procedūra suteikia galimybę gauti paprastus inžinerinius algoritmus, skirtus spręsti šilumos laidumo lygtį daugiasluoksnėje srityje. Stacionariu atveju įmanoma nustatyti tikslų skirtumų schemos sprendinį. Darbe nagrinėtas atvirkščias uždavinys. Skaitinio eksperimento metu gauti šilumos laidumo koeficientai ir temperatūros vidiniuose sluoksniuose priklausomai nuo išorinių plokštės duomenų. First Published Online: 14 Oct 2010